DREPTURILE OMULUI ÎN CONTEXT PROFESIONAL: INDIVIDUL CA ANGAJAT ÎN CÂMPUL MUNCII – MOTIVAȚIE, PERFORMANȚĂ, STARE DE BINE (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Human Rights in Professional Context: The Individual as Employee at Work – Motivation, Performance, Well-Being.The professional context is highly relevant for the human’s existence. Nowadays the professional life and the individual’s accomplishments in all fields of activity are more and more valuable. Therefore, the modern western society individual is trained to understand better than ever before the value of their professional responsibility, systematic effort, professional efficiency, success, being no longer afraid of the failure’s consequences. Moreover, there is a closure connection between the individual’s motivation, their professional performance and their physical and psychological well-being.